Результати операції за Латарже під артроскопічним контролем - Головаха, Максим Леонідович; Кузнєцов, Богдан Анатолійович; Golovakha, M. L.; Kuznietsov, B. A. (My University, 2020)
На сьогодні сформоване уявлення щодо показань до застосування консервативних і хірургічних методів за умов нестабільності в плечовому суглобі. Зокрема, однією з актуальних технік у разі переднього та передньо-нижнього типів рецидивуючої нестабільності в плечовому суглобі з дефектом суглобової поверхні гленоїда є операція за Латарже. Незважаючи на значний історичний досвід застосування наведеної техніки в її відкритому варіанті [1, 2], чітке розуміння її анатомічного [3, 4] та біомеханічного обґрунтування [5, 6], ретроспективні спостереження різних клінічних груп пацієнтів упродовж тривалого часу [7–9], дані літератури стосовно ефективності її артроскопічної модифікації вказують переважно на теоретико-експериментальні дослідження [10] та містять обмежені клінічні огляди [11, 12]. Latarjet procedure is one of the relevant techniques for the anterior and antero-inferior type of recurrent instability at the shoulder joint with a defect of the articular surface of the glenoid. A deeper study requires arthroscopic modification of this operation to assess its clinical effectiveness. Objective: to conduct a comparative analysis of open and arthroscopic Latarjet procedure, to evaluate intraoperative and postoperative complications and side effects of this surgical technique. Methods: a prospective randomized study was conducted, which included 30 patients: after open Latarjet procedure — 16 (53.3 %), arthroscopic — 14 (46.7 %). The results were evaluated at 3 and 6 weeks, 3–4 and 6–9 months after the operation using x-ray methods, computed tomography, Walch-Duplay and Rowe scales, and intraoperative and postoperative complications were also analyzed. In the case of arthroscopic technique, an increase in the volume of external rotation during the adduction and abduction of the shoulder, an open technique — a decrease (p = 0.01). A decrease of the volume during internal rotation (spinous process) was revealed with the use of both techniques, but w ith better r esults a fter a rthroscopic ( p = 0 .02). C onclusions: when using arthroscopic and open methods of Latarjet procedure, a statistically confirmed equal improvement in results is observed with recurrent instability of the shoulder joint. The results indicate the clinically significant advantages of restoring the function of the shoulder joint, especially external rotation when using the arthroscopic technique of Latarjet procedure in comparison with the open technique.
The results of latarjet procedure under arthroscopy control
Keywords: плечовий суглоб; нестабільність; хірургічне лікування; shoulder joint; instability; surgical treatment